2018
DOI: 10.3389/fevo.2018.00004
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Egg Predators and Food Availability Interactively Affect Maternal Investment in Egg Chemical Defense

Abstract: Invasive species commonly predate the offspring of native species and eggs are the life stage most vulnerable to this predation. In many species with no maternal care, females can alter the phenotype of eggs to protect them, for instance through chemical defense. In ladybirds egg alkaloids deter predators, including invasive predatory species of ladybirds, but conversely may attract cannibals who benefit from the consumption of eggs with higher alkaloid levels. Invasive predators tend to be more abundant where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…However, in the absence of an understanding of the roles of the two alkaloids, it is hard from the perspective of a predator to interpret whether the different colour pattern morphs really convey any information about relative distastefulness and toxicity. It should also be borne in mind that many other factors play a role in colour pattern polymorphism apart from chemical defence (Sloggett & Honěk 2012; Briolat et al 2019)There was no clear relationship between maternal alkaloid and egg alkaloid in this study, except possibly for adalinine, where the relationship was positive Paul et al (2015Paul et al ( , 2018. reported contradictory results for adaline: in A. bipunctata in their experiments: in one study, they found no correlation, whereas in another there was a positive relationship.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…However, in the absence of an understanding of the roles of the two alkaloids, it is hard from the perspective of a predator to interpret whether the different colour pattern morphs really convey any information about relative distastefulness and toxicity. It should also be borne in mind that many other factors play a role in colour pattern polymorphism apart from chemical defence (Sloggett & Honěk 2012; Briolat et al 2019)There was no clear relationship between maternal alkaloid and egg alkaloid in this study, except possibly for adalinine, where the relationship was positive Paul et al (2015Paul et al ( , 2018. reported contradictory results for adaline: in A. bipunctata in their experiments: in one study, they found no correlation, whereas in another there was a positive relationship.…”
mentioning
confidence: 55%
“…In this study of A. decempunctata, there was a tendency for alkaloids to decline with female fecundity, though not signi cantly. Data on adaline in A. bipunctata is also contradictory on this point(Paul et al 2015(Paul et al , 2018 but in one case, they also observed a negative relationship(Paul et al 2018). In both studies of A. bipunctata, adalinine was not quanti ed, making a direct comparison with our study di cult, but if a relationship, albeit weak, with female parameters exists, for adaline in A. bipunctata and adalinine (but not adaline) in A. decempunctata, then this might re ect the relative importance of the alkaloids in the two species.…”
mentioning
confidence: 99%
“…These chemicals make the eggs unpalatable (Cottrell 2004;Sato & Dixon 2004) and can also be found in older life stages of coccinellids (Pasteels et al 1973;Dixon 2000). On the other hand, the alkaloids that work as a defence against intraguild predation might be attractive to conspecific individuals, which are not affected by those compounds facilitating cannibalism (Omkar & Gupta 2004;Kajita et al 2010;Paul et al 2018).…”
Section: Discussionmentioning
confidence: 99%